2022
DOI: 10.3390/ijms232112895
|View full text |Cite
|
Sign up to set email alerts
|

Rhamnetin, a Natural Flavonoid, Ameliorates Organ Damage in a Mouse Model of Carbapenem-Resistant Acinetobacter baumannii-Induced Sepsis

Abstract: In sepsis, the persistence of uncontrolled inflammatory response of infected host cells eventually leads to severe lung and organ failure and, ultimately, death. Carbapenem-resistant Acinetobacter baumannii (CRAB), causative bacteria of sepsis and lung failure in acute cases, belongs to a group of critical pathogens that cannot be eradicated using the currently available antibiotics. This underlines the necessity of developing new modes of therapeutics that can control sepsis at the initial stages. In this stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 63 publications
0
12
0
Order By: Relevance
“…The flavonoid polyphenol quercetin upregulates neuron gene expression [ 86 ]. The flavonoid rhamnetin decreases organ failure in Gram-negative bacterial sepsis in mice [ 87 ]. Similarly, the flavonoids luteolin and icariin increase survival against polymicrobial sepsis [ 36 , 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…The flavonoid polyphenol quercetin upregulates neuron gene expression [ 86 ]. The flavonoid rhamnetin decreases organ failure in Gram-negative bacterial sepsis in mice [ 87 ]. Similarly, the flavonoids luteolin and icariin increase survival against polymicrobial sepsis [ 36 , 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…Studies revealed that it can be a promising and cheap source of flavonoids. , Flavonoids have great potential as anticancer and anti-inflammatory pharmaceuticals, as well as antiaging agents in cosmetics. Examples of these compounds, extracted from plants with DESs, are presented in Table . , …”
Section: The Most Interesting Bioactive Compounds Extracted With Dess...mentioning
confidence: 99%
“…We identified the anti-inflammatory activities of various flavonols, such as isorhamnetin, rhamnetin, and tamarixetin, which inhibit the production of pro-inflammatory cytokines in LPS-stimulated macrophages. [30][31][32]. In particular, rhamnetin, an O-methylated flavonol, can reduce inflammatory responses in the E. coli and CRAB-induced septic shock mouse model [31] (Figure 1).…”
Section: Introductionmentioning
confidence: 99%
“…[30][31][32]. In particular, rhamnetin, an O-methylated flavonol, can reduce inflammatory responses in the E. coli and CRAB-induced septic shock mouse model [31] (Figure 1). However, the underlying mechanism for the anti-inflammatory and antiseptic effects of rhamnetin has not been elucidated yet.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation